Solitary fibrous tumor of the pleura in a 22-year-old woman: a case report. Issue 9 (September 2020) - Sun, Nina; Wang, Jingluan; Cheng, Zhaozhong; Han, Weizhong; Li, Guo; Tong, Li
Solitary fibrous tumor of the pleura (SFTP) is a rare disease, and most published case reports are in patients over 40 years old. We report a case of SFTP in a 22-year-old woman. The imaging features were observed using contrast-enhanced computed tomography (CT), and histomorphological features were evaluated using pathology and immunohistochemistry. The CT showed a mass in the pleura inside the ninth rib on the left. Pathological results of percutaneous puncture in the chest suggested the possibility of solitary fibroma. The patient underwent surgical resection, and the tumor measured 2.5 × 1.5 × 1.5 cm with an intact capsule. Pathological examination revealed a spindle cell tumor, and immunohistochemistry showed strong positive staining for CD34 and STAT6, consistent with typical solitary fibroma. Although SFTP is rare in young patients, early diagnosis and intervention are needed to avoid the possibility of future complications.